Information Technology in a Democracy - Westin Alan F (Harvard University Press, 1971)
Prologue: Of Technological Visions and Democratic Politics, Descriptions of the Developing Systems by Their Advocates, The Databank and Information Systems Route, The Management Science Route, Planning and Programming and Budgeting System (PPB), Systems Analysis and Operations Research, The Corporate Consultants, ''Control Technology'' in a Democracy: The Broad Socio-Political Debate, The Information Function in Organizational Decision-Making, Emerging Information Systems: The Policy Debates, Databanks, Management Science Techniques, Bibliography, Index.